2020
DOI: 10.3390/jcm9103206
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in 6.5-Year-Old Children Born Extremely Preterm

Abstract: Physical activity (PA) can prevent cardiovascular diseases. Because of increased risks of impairments affecting motor activity, PA in children born preterm may differ from that in children born at term. In this prospective cohort study, we compared objectively measured PA in 71 children born extremely preterm (<27 weeks gestational age), to their 87 peers born at term, at 6.5 years of age. PA measured with accelerometer on the non-dominant wrist for 7 consecutive days was compared between index and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…According to gender, it seems that there are differences between boys and girls, with higher values of MVPA in boys, regardless of whether they are measured during the week or on weekends ( Aibar et al, 2014 ). Other studies have not identified differences according to gender in teenagers ( Manzano-Sánchez and Valero-Valenzuela, 2018 ) or children ( Svedenkrans et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…According to gender, it seems that there are differences between boys and girls, with higher values of MVPA in boys, regardless of whether they are measured during the week or on weekends ( Aibar et al, 2014 ). Other studies have not identified differences according to gender in teenagers ( Manzano-Sánchez and Valero-Valenzuela, 2018 ) or children ( Svedenkrans et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…Our study measured PA comprehensively by considering both accelerometer-measured and parent-reported PA across a range of movement behaviours, facilitating translation into clinical practice and health promotion strategies for preschool-aged children born VP. The first to investigate associations between perinatal risk factors and later PA in children born EP, Svendenkrans and colleagues similarly found that severe neonatal brain injury (IVH grade III/IV and/or periventricular leucomalacia) was a predictor of less accelerometer-measured MVPA in 6-year-old children, while little correlation found between GA or severe BPD with later MVPA 6…”
Section: Discussionmentioning
confidence: 99%
“…Concerningly, recent evidence suggests that preschool/early school-aged children born very preterm (VP; <32 weeks’ gestation) complete less PA than term-born children 5–7. Few studies have investigated effects of PA on development for preschool-aged children born VP, despite greater rates of adverse developmental outcomes for this group 5 8 9.…”
mentioning
confidence: 99%
“…Prior studies on the physical activity of children with BPD have demonstrated lower participation in physical activity through self‐report 5,7 . Other studies have demonstrated decreased time spent in moderate‐to‐vigorous physical activity (MVPA) in some subpopulations of preterm infants, particularly boys, when compared to term matched peers 8–10 . Studies examining exercise tolerance and aerobic capacity have also been mixed, showing both normal and reduced exercise tolerance 11,12 as well as both similar and reduced aerobic capacity 7,8 in children born preterm (some independent of the diagnosis of BPD 8 ) when compared to children born at term.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Other studies have demonstrated decreased time spent in moderate-to-vigorous physical activity (MVPA) in some subpopulations of preterm infants, particularly boys, when compared to term matched peers. [8][9][10] Studies examining exercise tolerance and aerobic capacity have also been mixed, showing both normal and reduced exercise tolerance 11,12 as well as both similar and reduced aerobic capacity 7,8 in children born preterm (some independent of the diagnosis of BPD 8 ) when compared to children born at term. Children with BPD have been shown to have pulmonary function abnormalities including reduced forced expiratory volume in 1 s (FEV1) 7,13,14 and mid-expiratory flows (FEF 25-75 ), 13 moderate-to-severe airflow obstruction and hyperinflation.…”
Section: Introductionmentioning
confidence: 99%